2013
DOI: 10.1007/s12664-013-0376-4
|View full text |Cite
|
Sign up to set email alerts
|

Cryptogenic cirrhosis is the leading cause for listing for liver transplantation in Sri Lanka

Abstract: Hepatitis B and C are rare in Sri Lanka. Nonalcoholic fatty liver disease is increasing in the country. Eighty-one patients referred for liver transplantation (LT) over a period of 18 months were prospectively evaluated. Ninety-two percent (n = 74) were males. Cryptogenic cirrhosis was the leading indication for LT (58%, n = 47) followed by alcohol in 27% (n = 33). Hepatitis B and C were not seen in our cases. The liver biochemistry and clinical status of cirrhosis were similar in cryptogenic and alcoholic cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 9 publications
2
21
0
Order By: Relevance
“…8 We previously reported that 63% of cases referred for liver transplantation were related to NASH-cirrhosis. 9 We also reported that 59% of the hepatocellular carcinomas were secondary to cryptogenic or NASH-cirrhosis. 10 Large percentages (45%) of our liver donors are rejected as a result of the presence of NAFLD.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…8 We previously reported that 63% of cases referred for liver transplantation were related to NASH-cirrhosis. 9 We also reported that 59% of the hepatocellular carcinomas were secondary to cryptogenic or NASH-cirrhosis. 10 Large percentages (45%) of our liver donors are rejected as a result of the presence of NAFLD.…”
Section: Introductionmentioning
confidence: 87%
“…Instead, alcoholic and cryptogenic or NASH‐related forms of cirrhosis predominate . We previously reported that 63% of cases referred for liver transplantation were related to NASH‐cirrhosis . We also reported that 59% of the hepatocellular carcinomas were secondary to cryptogenic or NASH‐cirrhosis .…”
Section: Introductionmentioning
confidence: 98%
“…Hepatitis B and C are extremely rare. The majority of the cases are related to NAFLD [6,7] . Others are either alcohol related or the result of a combination of both aetiologies.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on nonalcoholic fatty liver disease and cirrhosis from Sri Lanka have shown that nonalcoholic fatty liver disease is common (a prevalence of >30% in adults in an urban population) and that cryptogenic cirrhosis (probably related to NASH) is a leading cause of cirrhosis and referral for liver transplantation [7,8,14] . In this study, high alcohol consumption was significantly more common in patients with diffuse HCC.…”
Section: Discussionmentioning
confidence: 99%
“…In Sri Lanka, hepatitis B and C are uncommon. Most of our cirrhotic diseases are related to alcoholic or nonalcoholic steatohepatitis (NASH) or a combination of both [7,8] . With this background, we have noticed that a larger proportion of our HCC are diffuse in type.…”
Section: Introductionmentioning
confidence: 99%